Sosiologi Persekolahan - Malik, Abdul (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
The development of the school as an educational practice as long as it shows a lot of issues that are wrapped around the school. One of them is the difficulty of school to find recipes to produce the smart and good school output, to build this requires partnership and configuration changes. The configuration is the influence of the school became an interesting study, because it tends to change its effects. The school as the initiator needs to build a coalition that synergistic between schools, families, and communities.